Müller cyst: report of a case in pregnancy - Lara, Raúl D.; Araiza, Junior J.; López, Tecaztipocla E.; Garay, Maria del R.; Tolentino, Maria I.; Barbabosa, Jorge A. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Müller cysts are alterations in the development of sexual cords and remain as malformations associated with them. They can occur in many morphological varieties. In the case of pregnancy, vaginal tumors can complicate labor because they cause obstruc-tion of the canal. During labor, these alterations can complicate the diagnosis and proper management of pregnancy. A 22-year-old female, who came to the hospital at 30.1 weeks of gestation for the first time, due to obstetric pain, vaginal tumor was detected, the patient triggered preterm labor, which did not address medical management based on oral and intravenous uteroinhibitors, so a cesarean is decided, later in the puerperium magnetic resonance was performed finding a defect in the vaginal wall, compatible with probable Müller’s cyst. Due to its low frequency but high impact on pregnancy, vaginal tumors are a diagnostic and therapeutic challenge, due to their embryological origin should be detected and advise on the consequences of them. As a result, some other alterations may coexist, which is why complementary studies are essential. In the pregnancy protocol, the proper location of the cysts guides us to a specific embryological origin, as well as a preventive intervention can be planned in cases like this. If these patients are asymptomatic, surgical intervention is not required, much less during pregnancy unless an obstetric indication for interruption is determined.